Development of a novel fault management in distribution system using distribution automation system in conjunction with GSM communication - Ab Ghani, Mohd Ruddin; Mat Hanafiah, Mohd Ariff; Raman, Siti Hajar; Wan Jusoh, Wan Nor Shela Ezwane; Baharudin, Zikri Abadi (ETPub, 2013)
The paper develops and implement a novel fault management in distribution automation systems (DAS) at low voltage to enhance reliability of power for the consumers. The proposed fault management system is design based on GSM (global system for mobile) communication. The system has been equipped with current sensor as field data interface devices, microcontroller as remote terminal unit, GSM as communication network, computer as master terminal unit and visual basic as human interface (HMI) software. A fault management strategy is also designed to find out the fault location effectively without human intervention after a fault occurred. The laboratory results are compared with the simulation results to make the final conclusion on the functionality of the algorithm.